2018
DOI: 10.1002/fsn3.740
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties, ACE/renin inhibitory activities of pigeon pea hydrolysates and effects on systolic blood pressure of spontaneously hypertensive rats

Abstract: Legumes are rich sources of protein in human diet and their consumption has been associated with the prevention of chronic diseases attributable to their bioactive components. Pigeon pea (Cajanus cajan) is an underutilized legume with relatively high protein content (~24%). Protein hydrolysates were prepared from pea isolate by enzymatic hydrolysis using pepsin and pancreatin. Hydrolysates were evaluated for their amino acid composition, antioxidant properties, in vitro and in vivo antihypertensive properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 33 publications
4
55
3
Order By: Relevance
“…The total contents of the activity‐associated amino acids in pigeon pea protein was 32%, which was similar to the amounts in the hydrolysates, PepH (35%), PapH (32%), and TheH (33%). Compared to a previously reported amino acid composition (Olagunju et al, , ), the pigeon pea protein in our study had higher amounts of Pro and Val, and lower amounts of Leu and Phe, although the total composition of the activity‐related amino acids are similar. Despite the similarity, particular amino acid composition of the hydrolysates in our study were different (e.g., PapH > PepH > TheH for Pro content), possibly due to the specificity of proteases used in hydrolyzing the pigeon pea proteins.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…The total contents of the activity‐associated amino acids in pigeon pea protein was 32%, which was similar to the amounts in the hydrolysates, PepH (35%), PapH (32%), and TheH (33%). Compared to a previously reported amino acid composition (Olagunju et al, , ), the pigeon pea protein in our study had higher amounts of Pro and Val, and lower amounts of Leu and Phe, although the total composition of the activity‐related amino acids are similar. Despite the similarity, particular amino acid composition of the hydrolysates in our study were different (e.g., PapH > PepH > TheH for Pro content), possibly due to the specificity of proteases used in hydrolyzing the pigeon pea proteins.…”
Section: Resultscontrasting
confidence: 93%
“…A major challenge of the in silico approach is the dearth of in vitro analysis to confirm bioactivity (Agyei et al, ). Using the classic approach, recent studies reported that fermented/hydrolyzed pigeon pea seeds/flour have strong potential for exploration as antioxidative and antihypertensive food ingredients (Nawaz et al, ; Olagunju, Omoba, Enujingha, Alashi, & Aluko, ; Olagunju, Omoba, Enujingha, Alashi, & Aluko, ; Olagunju et al, ). The objectives for this study were to use the bioinformatics approach to assess the potential of nutrient reservoir (storage) proteins in pigeon pea as precursors of DPP‐4‐inhibiting peptides, and to evaluate the relationship between structural features of the proteins and biofunctional parameters of released peptides.…”
Section: Introductionmentioning
confidence: 99%
“…It is common practice to use a model organism in the assessment of the anti-oxidative stress capacity of compounds [ 8 ]. Therefore, an oxidation-damaged model of C. elegans induced by paraquat was constructed to detect the antioxidant activity of the hydrolysate.…”
Section: Resultsmentioning
confidence: 99%
“…The damaging effects of excessive ROS could be reduced by intracellular antioxidant enzymes including superoxide dismutases (SODs), glutathione peroxidases (GPXs), and catalases (CATs), as well as some non-enzymatic antioxidant molecules such as glutathione (GSH), vitamin C, and E [ 5 , 6 ]. However, subjected to severe stressors such as toxins and oxidants, the endogenous antioxidants may not be sufficient to counteract the destructive effects of ROS, and the intake of dietary antioxidants has been reported to prevent oxidative injury and maintain redox balance [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pearl millet protein isolate (PMPI), finger millet protein isolate (FMPI), and green sorghum millet protein isolate (GSMPI) were enzymatically hydrolyzed in vitro using previously reported method (Olagunju et al., 2018) with slight modifications. Protein isolates (1 g) were dissolved in distilled water (DW) (50 ml) and kept for 10 min into water bath at 80°C to denature the protein.…”
Section: Methodsmentioning
confidence: 99%